Interdisciplinary Citizen Science and Design Projects for Hazard and Disaster Education. Issue 1 (March 2019) - Masterson, Jaimie Hicks; Meyer, Michelle Annette; Ghariabeh, Nasir; Hendricks, Marccus; Lee, Ryun Jung; Musharrat, Saima; Newman, Galen; Sansom, Garett; Zandt, Shannon Van
Disaster science is increasingly incorporating interdisciplinary methods and participatory research techniques. Yet, traditional higher education programs remain focused on lecture. More examples of educational efforts that meet the needs of future researchers and practitioners to foster collaboration across disciplines and with communities are needed. This paper describes one such effort that included three projects co-designed and co-led by university students, faculty, and community residents to address flooding challenges in socially vulnerable neighborhoods. This paper provides an overview of the educational programs, the three projects, and the feedback from graduate and undergraduate students who helped initiate these efforts, and discusses the benefits and challenges for similar interdisciplinary and participatory educational programs. Benefits for students include increased interdisciplinary dialogue, improved science communication, increased research participation, real-world research experience, and awareness of resident perspectives and knowledge. Challenges include a lack of cultural competency among students, time needed to earn resident trust, and mismatched community, academic, and student schedules.